2012
DOI: 10.5114/wo.2012.31777
|View full text |Cite
|
Sign up to set email alerts
|

Atypical dissemination of lung cancer to the adrenal gland and to the spleen

Abstract: Metastases of lung cancer to such organs as the liver, bones or to the central nervous system appear to be a frequent complication of this disease. At the same time, metastases to the adrenal gland are found less frequently. Metastases of lung cancer to the spleen are a great rarity and they are described sporadically. Our report presents a unique case of left lung cancer with simultaneous metastases to the adrenal gland and to the spleen. All the presented lesions were diagnosed by ultrasound guided biopsy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…But our experience with the ultrasound-guided fine-needle biopsy of a spleen showed that, if performed under ultrasound guidance with appropriate blood clotting parameters, splenic biopsy in the evaluation of new or recurrent neoplasm is a minimally invasive procedure with low complication rates and a high diagnostic yield. The safety of spleen biopsy was confirmed by others authors as well [17][18][19][20].…”
Section: Methodssupporting
confidence: 65%
See 3 more Smart Citations
“…But our experience with the ultrasound-guided fine-needle biopsy of a spleen showed that, if performed under ultrasound guidance with appropriate blood clotting parameters, splenic biopsy in the evaluation of new or recurrent neoplasm is a minimally invasive procedure with low complication rates and a high diagnostic yield. The safety of spleen biopsy was confirmed by others authors as well [17][18][19][20].…”
Section: Methodssupporting
confidence: 65%
“…[4][5][6]. In 1 case the tumor spread into the spleen as well as into the left adrenal gland and this case was published already separately [20]. The biopsy had to be done twice in 2 cases in order to obtain clear histopathological results.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Having vast experience in performing biopsies, the authors decided to take biopsies of metastatic deposits located in the adrenal glands [12][13][14][15][16]. These deposits were identified on routine computer tomography (CT) scans in patients diagnosed with lung cancer.…”
Section: Introductionmentioning
confidence: 99%